Estágio supervisionado obrigatório laminite equina: relato de caso - Azevedo Neto, Claudomiro Ovidio de (Universidade Federal Rural do Semi-Árido, 2019)
The mandatory stage was carried out at the Jerônimo Dix-Huit Rosado Maia Veterinary Hospital (HOVET), located at the Federal Rural Semi-Arid University (UFERSA), MossoróRN campus. The traineeship period was from November 12, 2018 to February 9, 2019, in the Medical and Surgical Department of Large Animals, with a total workload of 330 hours. The objective was to follow the routine of a veterinary hospital with a high casuistry, improving the theoretical-practical knowledge, through the experience in the hospital environment and to approach a case report on an equine with laminitis. Accidentally, on November 15, 2018 the animal had eaten chicken bed. Upon arrival at the hospital on November 19, 2018, the patient was in the state of the station and mucous membranes, with suspicion of laminitis, in the specific examination performed in the gastrointestinal tract presented reflux and bulging in the flank and the examination of the locomotor system can be palpation in the region above the crown of the hull. Already on the first day of treatment the animal underwent cryotherapy. The initial protocol for laminitis was phenylbutazone (4.8 mg / kg, IV, BID, for seven days), acetylsalicylic acid (10 mg / kg, VO, SID for seven days), acepromazine (0.2 mg / kg , IM, TID, for seven days), flunixin meglumine (0.27 mg / kg, IM, TID, for seven days) and omeprazole (2 mg / kg, VO, SID, for fifteen days). The animal was primed with horseshoe with support of ranilha, during the period of internment the bay of the animal had woodwork. The patient was discharged on 5 December. The completion of the Mandatory Supervised Internship allowed a greater experience in the Medical and Surgical Clinic of Large Animals, favoring the theoretical and practical development fundamental for the profession of the future Veterinarian, in the animal of the present case study, the accomplishment of cryotherapy, associated to the directed treatment to improve digital blood flow, was considered a good option for recovery of this, however, it is worth noting that it is an expensive and time-consuming treatment.
Monografia
Keywords: Sepse bacteriana; Distúrbios metabólicos; Peso excessivo; Crioterapia; Ferrageamento; Bacterial sepsis; Metabolic disorders; Excessive weight; Cryotherapy; Ferration; CIENCIAS AGRARIAS::MEDICINA VETERINARIA